New index of abdominal obesity, a body shape index, is BMI-independently associated with systemic arterial stiffness in real-world Japanese population - Nagayama, Daiji; Watanabe, Yasuhiro; Yamaguchi, Takashi; Maruyama, Mitsuya; Saiki, Atsuhito; Shirai, Kohji; Tatsuno, Ichiro (International journal of clinical pharmacology and therapeutics, 2020)
To clarify that the new index of abdominal obesity, a body shape index (ABSI), is associated with obesity-related metabolic disorders and arterial stiffness. We analyzed the cross-sectional data from 62,514 Japanese subjects (mean age 44.4 years, mean body mass index (BMI) 22.2 kg/m ) without a past history of cardiovascular disease, stroke, or treatment for obesity-related metabolic disorders. Various body adiposity indices including BMI, waist circumference (WC), and ABSI were evaluated for abilities to indicate metabolic disorders and arterial stiffness assessed by cardio-ankle vascular index (CAVI). WC, WC/height ratio, and WC/BMI ratio correlated with BMI regardless of gender or obesity, whereas ABSI hardly correlated with BMI. ROC analyses demonstrated that ABSI had the highest discriminatory power in predicting high CAVI (≥ 90 percentile) compared to other body adiposity indices, and the cut-off value was 0.080. Increases in ABSI as well as BMI reflected severity of metabolic disorders. After adjusting for confounders identified by multiple regression analysis, adjusted CAVI correlated positively with ABSI, whereas an inverted relationship was observed between adjusted CAVI and BMI. Additionally, the contribution of high ABSI (≥ 0.080) for high CAVI was independent of gender, age, obesity, and obesity-related metabolic disorders in the multivariate logistic regression model. ABSI is an easily calculated index of abdominal obesity which reflects metabolic disorders and systemic arterial stiffening, and may be useful in primary health screening even without any medical equipment for visceral fat quantification.